Is Physical Evidence Still Valid? A Study of Low Cost Carriers in Indonesia - Soelasih, Yasintha (Gadjah Mada International Journal of Business, 2015)
Physical evidence has been widely accepted as variable that has impact on satisfaction, specifically in airline service. However, this study showed some opposite result for low cost airlines in Indonesia. It revealed that physical evidence has no effect on the passengersâ satisfaction but the fares and its service quality to passengers.â This study collected sample of 317 passengers from commercial domestic flights at terminal 1, 2, and 3 at Soekarno Hatta airport in Cengkareng, Indonesia. The variables used in this study were: fares, service quality, physical evidence, passengersâ satisfaction levels and repeat buying. Two variables, i.e.: service quality and physical evidence were treated as second order. This study used Structural Equation Modeling (SEM) for verification analysis. The result revealed that there was no effect of physical evidence on the passengersâ satisfaction. It also found that repeat buying demonstrated the passengersâ satisfaction.